The management of light chain (AL) amyloidosis in Europe: clinical characteristics, treatment patterns, and efficacy outcomes between 2004 and 2018 - Palladini, Giovanni; Schönland, Stefan; Merlini, Giampaolo; Milani, Paolo; Jaccard, Arnaud; Bridoux, Frank; Dimopoulos, Meletios A.; Ravichandran, Sriram; Hegenbart, Ute; Roeloffzen, Wilfried; Cibeira, M. Teresa; Agis, Hermine; et al. (Blood cancer journal, 2023)
Systemic light-chain (AL) amyloidosis is a rare and debilitating disease. Advances have been made in new treatments in recent years, yet real-world data on the management of the disease are scarce. EMN23 is a retrospective, observational study of patients who initiated first-line treatment in 2004-2018 in Europe, presenting the demographics, clinical characteristics, treatment patterns, and outcomes, from 4480 patients. Regimens based on bortezomib were the most frequently used as first-line therapy; only 6.2% of the patients received autologous stem cell transplant. Hematologic responses improved post-2010 (67.1% vs 55.6% pre-2010). The median overall survival (OS) was 48.8 (45.2-51.7) months; 51.4 (47.3-57.7) months pre-2010 and 46.7 (41.3-52.2) months post-2010. Early mortality was 13.4% and did not improve (11.4% vs 14.4% pre- and post-2010); furthermore, it remained high in patients with advanced cardiac disease (over 39% for stage IIIb). There was a significant improvement for stage IIIa (14.2 vs 30.7 months, p = 0.0170) but no improvement for stage IIIb patients (5.0 vs 4.5 months). This European real-world study of AL-amyloidosis emphasizes the unmet needs of early diagnosis, and the lack of improvement in survival outcomes of the frail stage IIIb population, despite the introduction of new therapies in recent years.